2013
DOI: 10.1002/phy2.40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prior acute exercise on circulating cytokine concentration responses to a high-fat meal

Abstract: High-fat meal consumption alters the circulating cytokine profile and contributes to cardiometabolic diseases. A prior bout of exercise can ameliorate the triglyceride response to a high-fat meal, but the interactive effects of exercise and high-fat meals on cytokines that mediate cardiometabolic risk are not fully understood. We investigated the effects of prior exercise on the responses of circulating tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-8, leptin, retinol-binding protein 4 (RBP4), vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Similarly, our hypothesis predicting lower inflammation in the EX group as compared to CON, was not supported. It has been previously shown that PPL is not always an accurate predictor of postprandial inflammation [ 19 ] and this was reinforced in the current study. Furthermore, there were no group differences between EX and CON when comparing changes in inflammatory markers over the course of the postprandial period, aside from the group x time interaction for sVCAM-1, which increased in the EX group as compared to CON.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, our hypothesis predicting lower inflammation in the EX group as compared to CON, was not supported. It has been previously shown that PPL is not always an accurate predictor of postprandial inflammation [ 19 ] and this was reinforced in the current study. Furthermore, there were no group differences between EX and CON when comparing changes in inflammatory markers over the course of the postprandial period, aside from the group x time interaction for sVCAM-1, which increased in the EX group as compared to CON.…”
Section: Discussionsupporting
confidence: 77%
“…Prolonged elevation of postprandial triglycerides may lower HDL cholesterol [ 17 ] and increase concentrations of small, dense, atherogenic, LDL cholesterol and chylomicron remnants [ 18 ]. However, it has been shown that prior exercise may be effective at lowering triglycerides while having no effect on the inflammatory response to a HFM [ 19 , 20 ]. Given that both of these prior studies used a bout of exercise that was completed the day before ingestion of the HFM, and therefore far in advance of the HFM, potential anti-inflammatory benefits of the acute exercise may not have been observable.…”
Section: Introductionmentioning
confidence: 99%
“…A separate study found a postprandial walk of only 30 min was also effective for attenuating PPL [103]. Other studies that have tested recreational exercisers have shown that these individuals may require energy expenditures in the 600-900 kcal range in order to attenuate PPL [104, 105]. Therefore, it appears that individuals who exercise less frequently may need to expend less energy during exercise to attenuate PPL.…”
Section: Exercise Energy Expenditure Intensity and Energy Balance Anmentioning
confidence: 99%
“…Experimental studies aimed at reducing postprandial inflammation through exercise have focused primarily on moderate-to-high intensity pre-meal exercise [104, 105]. While these studies have found prior exercise to be effective for attenuating PPL, they have not found acute exercise to be effective for decreasing postprandial inflammation.…”
Section: Acute Exercise and Postprandial Inflammationmentioning
confidence: 99%
“…In a review written by Katsanos and Moffatt (2004), the authors estimated that between 600 and 700 kcals may need to be expended to produce an attenuated lipemic response. However, physically inactive individuals may achieve a reduction in lipemic response to a HFM with a smaller energy expenditure compared to physically active individuals (Katsanos and Moffatt 2004; Brandauer et al 2013). In fact, an energy expenditure as minimal as 300 to 500 kilocalories may elicit a reduction in lipemia in inactive participants when performed without caloric replacement following the exercise bout (Murphy et al 2000).…”
Section: Introductionmentioning
confidence: 99%